The development of an instrument to measure intrapreneurship: entrepreneurship within the corporate setting - Hill, Marguerite Elizabeth (Rhodes University, Faculty of Humanities, Department of Psychology, 2003)
"Intrapreneurship is not a choice, it is the only survival attitude" (Pinchot, 2000, p.75). In 1985 Pinchot coined the term 'intrapreneurship', short for intra-corporate entrepreneurship, which describes the practice of entrepreneurship within organisations. Intrapreneurship is increasingly becoming a term used in the business world to describe organisations that are willing to pursue opportunities, initiate actions, and emphasise new, innovative products or services. Due to the dynamic nature of modern organisations, it is imperative that organisations and their managers remain receptive to new ideas, approaches and attitudes. It is therefore the belief that rapid and cost-effective innovation is the primary source of lasting competitive advantage in the twenty-first century, leaving organisations no alternative but to become intrapreneurial or cease to exist. This thesis focuses on this need and examines ways in which intrapreneurship can be measured in organisations in order to provide a benchmark for further organisational development. A questionnaire (known as the Intrapreneurial Intensity Index) was designed and distributed to a sample of 500 employees working in large South African organisations, which classified themselves as 'forward-thinking' and aimed for an intrapreneurial 'type of thinking'. The results obtained from these questionnaires underwent item analysis, after which the questionnaire was redesigned in an electronic format. A pilot case study was then conducted in order to test the reliability of the instrument. Finally the questionnaire was redistributed to a sample of six organisations that are viewed as being 'intrapreneurial' and two that are regarded as being 'non-intrapreneurial'. The data from this sample was used to test the validity of the Intrapreneurial Intensity Index and to demonstrate its application. This study resulted in an instrument that can be used to ascertain the intensity of intrapreneurship present in a large organisation. Specifically, this instrument can provide an overall view of the organisation's intrapreneurial ability, as well as identify the specific areas in the organisation that require change or modification in order to become more intrapreneurial. This instrument provides a valuable means of identifying areas in need of organisational change, by determining an organisation's intrapreneurial properties in the organisation's core areas.
Keywords: Entrepreneurship; Psychology, Industrial; Organizational change